2022
DOI: 10.1007/s10815-022-02547-4
|View full text |Cite|
|
Sign up to set email alerts
|

Adaptive data-driven models to best predict the likelihood of live birth as the IVF cycle moves on and for each embryo transfer

Abstract: Purpose To dynamically assess the evolution of live birth predictive factors’ impact throughout the in vitro fertilization (IVF) process, for each fresh and subsequent frozen embryo transfers. Methods In this multicentric study, data from 13,574 fresh IVF cycles and 6,770 subsequent frozen embryo transfers were retrospectively analyzed. Fifty-seven descriptive parameters were included and split into four categories: (1) demographic (couple’s baseline chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Therefore, this study found a negative correlation in pregnancy outcome when the total FSH dose exceeded a certain dose. It was also found that frozen embryo transfer reversed the adverse influence of high FSH on LBR in fresh cycles, indirectly suggesting that it may be the endometrium receptivity that is adversely affected by the FSH dose 51 , 52 . Nevertheless, the mechanisms by which high FSH doses alter follicular development and endometrial tolerance need to be further explored.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, this study found a negative correlation in pregnancy outcome when the total FSH dose exceeded a certain dose. It was also found that frozen embryo transfer reversed the adverse influence of high FSH on LBR in fresh cycles, indirectly suggesting that it may be the endometrium receptivity that is adversely affected by the FSH dose 51 , 52 . Nevertheless, the mechanisms by which high FSH doses alter follicular development and endometrial tolerance need to be further explored.…”
Section: Discussionmentioning
confidence: 97%